(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aims to examine security systems borders and their impact on international relations during Al Rashideen and alamawi eras (11-132 AH / 632-750 CE). The aim of the study is to trace the border security systems and their impact on international relations during the Rashidun and Umayyad eras, as well as their contributions during the period under study. The study adopts the historical inductive method and the descriptive historical method. It includes an introduction to the systems related to military preparations during the Rashidun and Umayyad eras, and two main sections: The study consists of two sections. The first section addresses human and material border security systems during the Rashidun and Umayyad eras. The second section explores security systems and their impact on international relations during these two eras. The study found that border security systems played a significant role in protecting the Islamic state from external threats. The study also explored that they ensured border security, reinforced the principle of strength within the Islamic state, and instilled fear and respect in the hearts of internal and external enemies during the Rashidun and Umayyad eras. The study concluded that the border security systems had a positive impact on international relations between the Islamic state and neighboring states during the Rashidun and Umayyad eras. The Islamic state maintained a commanding presence and continuous respect, both politically and militarily.